Uporaba robotskih naprav v rehabilitacijski obravnavi pacientov po možganski kapi - Bizovičar, Nataša (Rehabilitacija (Ljubljana), 2022)
The field of rehabilitation robotics has been developing rapidly over the last two decades. This review article summarises current robotic systems for lower and upper limb rehabilitation in patients after stroke. When choosing a suitable robotic device for a particular patient, it is important to know the main features of the device, the patient's level of functioning and therapeutic goals. Robotic training has a beneficial effect on the motor recovery of upper limb, walking and balance function after stroke, while also reducing the workload of therapists. Whilst the benefit of these technologies over dose-controlled conventional rehabilitation are usually small, there is a role for them as part of a broader rehabilitation programme, where they may help to increase the intensity and amount of therapy delivered. Therefore, robotic devices are still mostly used only as part of a multidisciplinary rehabilitation program and cannot replace the work of therapists.
Keywords: motor recovery; motorično okrevanje; možganska kap; neurorehabilitation; nevrorehabilitacija; rehabilitacijska robotika; rehabilitation; rehabilitation robotics; Robotics; Stroke